Analysis of Residual Chlorine and Total Coliform on Consumers of Perumdam Maja Tirta, Mojokerto City - Bagus Reynaldi; Taty Alfiah (Journal of Community Based Environmental Engineering and Management, 2022)
This study aims to determine the concentration of residual chlorine and net total Coliform distributed by Perumdam Maja Tirta Water Supply Company and received by consumers. Water samples were taken from 7 locations on the distribution network a residential area of Perumdam Maja Tirta, the first sample taken at the reservoir of the Water Treatment Plant of Perumdam Maja Tirta and six samples from consumers. The residual chlorine concentration data and Total Coliform were mapped using Surfer 16 Software, producing an iso concentration map in the form of contour lines. The results showed that the concentration of residual water chlorine received by consumers of Perumdam Maja Tirta Mojokerto City ranged from <LoQ 0.1 mg/L to 0.3 mg/L. The further away from the IPA, the concentration of residual water chlorine decreased. Total Coliform parameters ranged from <1.8 – 240/100 ml in water received by consumers of Perumdam Maja Tirta Mojokerto City. There is a need to improve the quality of water services to consumers regarding water treatment and distribution.